Descriptive Study of Growth and Development of Toddlers Aged 2-4 Years as a Basis for Early Development Mapping at PAUD Vinolia Mojolangu - Nisa Ayu Yuliati; Herawati Mansur (International Journal of Health and Pharmaceutical (IJHP), 2026)
Growth and development of children aged 2–4 years are critical indicators in determining long-term health outcomes and school readiness. This period is considered the golden age, as rapid brain development occurs, making early detection of growth and developmental disorders essential. However, developmental screening coverage in Indonesia remains suboptimal, and monitoring in early childhood education settings often focuses more on physical growth than developmental aspects. This study aimed to describe the growth and developmental status of children aged 2–4 years using the Maternal and Child Health (MCH) Handbook and the Denver Developmental Screening Test (DDST) at PAUD Vinolia Mojolangu. A descriptive observational design was applied to 23 children. Growth was assessed using height-for-age (HFA), weight-for-age (WFA), weight-for-height (WFH), and body mass index-for-age (BMI-for-age) indicators. Developmental status was evaluated using the DDST, which measures four domains: gross motor, fine motor, language, and personal-social skills. The results showed that most children were classified as having normal growth based on WFH and BMI-for-age indicators. In terms of development, the majority demonstrated age-appropriate outcomes, with one child categorized as “suspect” in the personal-social domain. These findings indicate that integrated monitoring using the MCH Handbook and DDST is effective in identifying children's growth and developmental conditions comprehensively. Strengthening early detection through collaboration among healthcare providers, early childhood educators, and parents is recommended to ensure timely and appropriate interventions.